Deskripsi Kemampuan Berpikir Logis dan Pemahaman Konsep Sistem Hormon pada Siswa Kelas XI SMA - Herman Sopian (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2019)
This study aimed to obtain information about logical thinking ability and understanding of the concept of students on the hormonal system material. This study was conducted in class XI in one of the high schools in the Serang city. The method used is descriptive quantitative. This quantitative descriptive method to describe, explain and interpret the logical thinking ability and understanding of students on the hormonal system concept by using instruments such as diagnostic tests and about the three-tier test and test of logical thinking (TOLT). The sampling technique is done by cluster random sampling as many as 33 students. Based on the results obtained TOLT that categorized either proportional reasoning, reasoning control variable and low category correlational reasoning, and reasoning probability and combinatorial reasoning sufficient category. Based on the three-tier test results showed that students had difficulty understanding especially on subconcepts hormone function as well as differences in the hormone system and nervous system